Würde und Selbstbestimmung über den Tod hinaus - Duttge, Gunnar; Viebahn, Christoph (Universitätsverlag Göttingen, 2017)
Whilst the treatment of mortal remains was largely predetermined in previous generations as an essential part of their respective cultures, the significance of the commandment to respect "dignity" and "piety" has nowadays become more unclear. Modern pluralism makes guidelines of behavior questionable, for example concerning burial, autopsy, or the use of body parts for transplant, scientific or teaching purposes, if this has not been legitimized by the "self-determination right" of the individual. At the same time, the "informed consent" appears as a passepartout for any kind of handling a corpse, even though it may be controversial, as in a commercial public exhibition. The interdisciplinary volume, which resulted from the 2nd Göttinger Symposium of the Center for Medical Law, deals with the wide field of "correct" intercourse with a corpse from the perspective of theology and medicine philosophy, medical law, anatomy and law medicine.